Pengamalan nilai-nilai Pancasila sebagai landasan etis dalam kebijakan perlindungan perempuan dari kekerasan seksual - Brahmandika, Leonard (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
Pancasila is the ideology of the Indonesian nation, interpreted as an ethical system that contains moral values ​​that are the basis for creating social justice, harmony, and family. Lack of understanding and practice of Pancasila values ​​causes sexual violence. The purpose of this study is to examine in more depth how the practice of Pancasila values ​​as an ethical basis in policies to protect women from sexual violence. This study uses a descriptive method with data collection techniques through literature studies. The results of the study indicate that the practice of Pancasila values ​​is an effort to prevent acts of sexual violence. Pancasila values ​​contain awareness of moral attitudes and human behavior based on conscience and norms in society. Pancasila values ​​are used as a basis for making policies to protect women by paying attention to their rights as citizens. Cooperation between educational institutions, society and government in instilling Pancasila values ​​in society is very important. The aim is to provide an understanding to the public that it is important to practice Pancasila values ​​in life so that it can prevent acts of sexual violence.